UTILIZATION OF NATURAL IRON ORE FOR CATALYTIC REACTION OF (Pyroligneous acid) DERIVED FROM PALM KERNEL SHELLS - Muhammad Arifuddin Fitriady; Dieni Mansur; Sabar Pangihutan Simanungkalit (Pusbindiklat - LIPI, 2016)
The increasing of energy demand and environment awareness along with the depletion of fossil fuel imply that the future energy supply must be from the renewable energy source. One of the major renewable energy sources is biomass. Pyrolysis is a rapid decomposition of organic materials in the absence of oxygen resulting in pyrolysis oil, gas, and charcoal products. High water contents and instabilities such as viscosity increase and phase separation are the main problems of pyrolysis oil as a source of useful chemicals. The pyrolysis oil is separated into the oil phase and the pyroligneous acid. The pyroligneous acid contains a lot of chemical substances, that prohibit removal to the environment as a waste due to environmental pollution. Furthermore, pyroligneous acid needs to be treated to obtain the useful chemical. In this study, catalytic reaction of the pyroligneous acid, derived from pyrolysis process of palm kernel shells, was carried out over natural iron ores catalyst at 350 °C with W/F [W: the amount of catalyst bed (g) and F: the flow rate of feed (g h-1)] of 0.5 h. The analysis result showed that iron ores that treated by calcination at 285 °C had a higher ability for ketonization reaction of carboxylic acid compared to other catalysts. Even so, neither calcination up to 500 °C nor steam treatment of natural iron ores can significantly increase the activity of the catalyst for the ketonization reaction even though the BET surface area of the catalyst increased.